Practical Application of Museum Research and Prospects for Digitization of Museum Collections (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the practical dimensions of museum research and the future of digital transformation in the management of museum collections. Focusing on the Central State Museum of the Republic of Kazakhstan, the study examines how digitization processes can be improved by integrating advanced technologies such as artificial intelligence (AI), 3D scanning, and virtual reality (VR). Key terms—digitization, digitalization, and digital transformation—are analyzed in terms of their definitions, distinctions, and interconnectivity. Drawing on global examples from the Smithsonian Institution, the Rijksmuseum, and the Metropolitan Museum of Art, the article outlines a set of strategic recommendations to enhance the digital capacity of the Central Museum of Kazakhstan. These include monetizing digital products, expanding virtual exhibitions, and implementing AR/VR solutions.